AN ANALYSIS OF CRITICAL THINKING ASPECTS IN STUDENTS' DISCUSSION TEXTS - Rachmawati, Yuli (2015)
This study aimed to analyze critical thinking aspects reflected in students' Discussion texts and find how students' writing process contributed to students' critical thinking aspects in students' opinion. The critical thinking aspects examined in this study covered critical thinking elements mainly proposed by Emilia (2005) as well as critical thinking dispositions mainly proposed by Ennis (1996). This study employed a qualitative research design involving nine university students majoring in English Education. The data included students' texts obtained through the students' writing assignment and confirmation of critical thinking aspects obtained through interviews to the students. The texts were analyzed using a rubric synthesized from theories relevant to this study, while the interview results were analyzed by adapting the steps of analyzing qualitative data by Lodico et al. (2004). The findings revealed that all critical thinking aspects covered in this study appeared in the texts. High achievers' texts presented more critical thinking aspects than medium and low achievers' texts, particularly on argument and open-mindedness. The findings also showed that the students perceived that their writing process, particularly the pre-writing stage, contributed to all critical thinking aspects covered in this study. This study recommended that the teaching of Discussion texts should explore all stages of writing process, especially pre-writing stage, to help students write well-elaborated arguments. Keywords: critical thinking aspect, critical thinking element, critical thinking disposition, writing process, Discussion text Penelitian ini bertujuan untuk menganalisis aspek-aspek berfikir kritis pada teks diskusi siswa serta menginvestigasi bagaimana proses menulis berkontribusi pada aspek-aspek berfikir kritis siswa dalam pandangan para siswa. Aspek-aspek berfikir kritis yang dibahas dalam penelitian ini adalah elemen-elemen berfikir kritis yang sebagian besar diusulkan oleh Emilia (2005) serta disposisi berfikir kritis yang sebagian besar diusulkan oleh Ennis (1996). Penelitian ini menggunakan desain penelitian kualitatif yang melibatkan sembilan mahasiswa pada jurusan Pendidikan Bahasa Inggris. Data penelitian ini diambil dari teks diskusi siswa serta interview. Teks-teks tersebut dianalisis menggunakan rubrik yang disintesis dari teori - teori yang relevan dengan penelitian ini, sedangkan data dari interview dianalisis dengan mengacu pada langkah - langkah menganalisis data kualitatif yang diajukan oleh Lodico et al. (2004). Penelitian ini menemukan bahwa semua aspek berfikir kritis yang dibahas pada penelitian ini terdapat pada teks siswa serta tergambar pada interview terhadap siswa. Teks siswa peraih nilai tinggi menunjukkan lebih banyak aspek berfikir kritis dibandingkan teks peraih nilai tengah dan rendah, terutama dalam hal argumen dan sikap terbuka. Penelitian ini juga menemukan bahwa para siswa berfikir bahwa proses menulis mereka, terutama fase pre-writing, berkontribusi pada semua aspek berfikir kritis yang dibahas pada penelitian ini. Penelitian ini merekomendasikan pengajaran teks diskusi mengeksplorasi semua fase menulis, terutama fase pre-writing, untuk membantu siswa dalam menulis argumen yang terelaborasi. Kata kunci: aspek berfikir kritis, berfikir kritis, elemen berfikir kritis, disposisi berfikir kritis, proses menulis, teks diskusi